2022
DOI: 10.1021/acs.langmuir.2c00821
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Pickering Nanoemulsions Prepared Using Diblock Copolymer Nanoparticles: Effect of Nanoparticle Core Crosslinking, Oil Type, and the Role Played by Excess Copolymers

Abstract: A poly( N , N ′-dimethylacrylamide) (PDMAC) precursor is chain-extended via reversible addition–fragmentation chain transfer (RAFT) aqueous dispersion polymerization of diacetone acrylamide (PDAAM) to produce PDMAC 77 -PDAAM 40 spherical nanoparticles. Post-polymerization core-crosslinking of such nanoparticles was performed at 20 °C, and the resulting covalently stabilized nanoparticles survive exposure to methanol. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Moreover, our prior studies suggested that nanoparticle disintegration can occur at higher applied pressures, leading to the generation of individual diblock copolymer chains. , Thus such conditions are best avoided if genuine Pickering nanoemulsions are desired. In view of these preliminary observations, a nanoparticle concentration of 5% w/w and a single pass at an applied pressure of 20,000 psi were used for the remaining experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our prior studies suggested that nanoparticle disintegration can occur at higher applied pressures, leading to the generation of individual diblock copolymer chains. , Thus such conditions are best avoided if genuine Pickering nanoemulsions are desired. In view of these preliminary observations, a nanoparticle concentration of 5% w/w and a single pass at an applied pressure of 20,000 psi were used for the remaining experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical centrifugation was used to determine the volume-average size distribution for both fresh and aged Pickering nanoemulsions prepared using various NaI concentrations. We have shown that analytical centrifugation is well-suited for determining the long-term stability of both oil-in-water and water-in-oil Pickering nanoemulsions. Unlike DLS, analytical centrifugation subjects the nanoemulsions to droplet fractionation prior to detection and therefore offers higher resolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…56,60,63−65 Thus aqueous PISA enables the convenient synthesis of hydrophilic spherical nanoparticles that are suitable for the preparation of Pickering nanoemulsions. 13,[16][17][18]27,43 For example, Thompson and co-workers examined the relative stability of a series of n-alkane-in-water Pickering nanoemulsions prepared using sterically stabilized nanoparticles comprising a hydrophilic poly(glycerol monomethacrylate) (PGMA) block and a hydrophobic poly(2,2,2trifluoroethyl methacrylate) (PTFEMA) block. 16,27 Analytical centrifugation studies confirmed that nanoemulsions prepared using oils with higher aqueous solubility (e.g., n-octane or ndecane) were more susceptible toward Ostwald ripening during storage for up to 7 days at 20 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, their relatively high surface area makes them prone to droplet growth via Ostwald ripening. , For O/W nanoemulsions, This involves the diffusion of oil molecules from smaller droplets through the aqueous continuous phase to larger droplets over time. Although there are many literature reports on the formation of copolymer- or surfactant-stabilized nanoemulsions, there are surprisingly few studies focused on Pickering nanoemulsions. , , This is no doubt because the Pickering emulsifier should be typically 5–10 times smaller than the mean droplet diameter . Thus, droplets of (say) 200 nm diameter require nanoparticles of 20–40 nm diameter.…”
Section: Introductionmentioning
confidence: 99%